Long-term exposure of fine particulate matter air pollution and incident atrial fibrillation in the general population: A nationwide cohort study - Kim, In-Soo; Yang, Pil-Sung; Lee, Jinae; Yu, Hee Tae; Kim, Tae-Hoon; Uhm, Jae-Sun; Pak, Hui-Nam; Lee, Moon-Hyoung; Joung, Boyoung (International journal of cardiology, 2019)
Although many studies have linked elevations in fine particulate matter (PM2.5) air pollution to adverse cardiovascular outcomes, long-term exposures of PM2.5 on air pollution-related incident atrial fibrillation (AF) in general population have not yet been investigated well. We included 432,587 subjects of general population not diagnosed with AF from the Korean National Health Insurance Service-National Sample Cohort from 2009 to 2013. Medical records were screened from January 2002 to investigate the subjects' disease-free baseline period. They were followed until December 2013. We matched subjects' residential ZIP code with hourly measurements of air pollutant (particulate and gaseous) concentrations and meteorological (temperature and humidity) data during the study period. During 1,666,528 person·years, incident AF was observed in 5825 subjects (350/100,000 person·year). We found significant associations between incident AF and long-term average concentrations of PM2.5 (HR = 1.179[1.176–1.183] for 10 μg/m3 increments, p < 0.001), PM10 (HR = 1.034[1.033–1.036] for 10 μg/m3 increments, p < 0.001), and gaseous air pollutants during the study period. When dividing subjects into subgroups, these long-term exposures of PM2.5 effects were more profound in males (HR = 1.187[1.183–1.192], p < 0.001), older subjects (aged ≥ 60 years; HR = 1.194[1.188–1.200], p < 0.001), those who were obesity (body mass index ≥ 27.5 kg/m2, HR = 1.191[1.183–1.199], p < 0.001), subjects with previous myocardial infarction (HR = 1.203[1.186–1.221], p < 0.001), and history of hypertension (HR = 1.191[1.185–1.197], p < 0.001) (each interaction p < 0.05 compared to the opposite subgroup). Even in the Asian general population, long-term exposure of PM2.5 is associated with the increased incidence of new-onset AF. It is more profound in obese male subjects > 60-year old and who have a history of hypertension or previous myocardial infarction. •PM2.5, PM10 exposures are associated with incident AF even in general population.•10 μg/m3 increments of PM2.5 is associated with 17.9% increase of incident AF.•10 μg/m3 increments of PM10 is associated with 3.4% increase of incident AF.•Their correlations were also shown as concentration-responsive.•These associations were more profound in obese male subjects with aged ≥ 60.